2022
DOI: 10.2991/assehr.k.211229.048
|View full text |Cite
|
Sign up to set email alerts
|

High School Students’ Self-Regulated Learning and Academic Procrastination Level in Blended Learning Model: A Correlation Analysis

Abstract: The Covid-19 pandemic causes teachers to conduct limited face-to-face learning with online and offline (blended learning), impacting students' low self-regulated learning (SRL) and high academic procrastination (AP). This study aims to describe students' SRL and AP levels in the blended learning model and examine the relationship of them. Eight hundred thirty students of Senior High School in Ngoro Mojokerto, Indonesia, qualified as participants and provided responses to the SRL scale and AP scale instruments … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 4 publications
1
2
0
Order By: Relevance
“…The previously reported limitations in access to affordable Internet services and suitable digital devices have caused it difficult for the larger portion of students to participate in the online learning process (UNICEF, 2020). These findings were in line with previous studies conducted on SMA and SMK students in the same province this research was conducted, which reported medium levels of academic procrastination (Latipah et al, 2021;Habibi et al, 2022). This portrays that the greater curricular burden borne by MA students than by their SMA and SMK peers in Central Java did not necessarily make the former procrastinate to a greater degree than the latter.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…The previously reported limitations in access to affordable Internet services and suitable digital devices have caused it difficult for the larger portion of students to participate in the online learning process (UNICEF, 2020). These findings were in line with previous studies conducted on SMA and SMK students in the same province this research was conducted, which reported medium levels of academic procrastination (Latipah et al, 2021;Habibi et al, 2022). This portrays that the greater curricular burden borne by MA students than by their SMA and SMK peers in Central Java did not necessarily make the former procrastinate to a greater degree than the latter.…”
Section: Discussionsupporting
confidence: 91%
“…Following the description above, it is necessary to further scrutiny the students' academic procrastination during the COVID-19 pandemic. However, research among senior high school students in Indonesia is still limited to the non-Islamicbased school (Latipah et al, 2021;Habibi et al, 2022;Irawan and Widyastuti, 2022). Studies showed that 47.2% of senior high school (SMA) students in Temanggung engaged in a medium level of academic procrastination (Latipah et al, 2021), 34.3% of vocational high school (SMK) students in Bojonegoro demonstrated a medium level of academic procrastination (Irawan and Widyastuti, 2022), and 652 or 78.6% state senior high school (SMAN) students in Mojokerto engaged in a medium level of academic procrastination (Habibi et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation